Conceptual design of a high resolution, low cost x-band airborne synthetic aperture radar system - Chan, Yee Kit; Koo, Voon Chet; Lim, Tien Sze (PIERS, 2007)
This paper describes the conceptual design of a low cost airborne Synthetic Aperture Radar (SAR) capable to obtain high-resolution image. The proposed system is an X-band, single polarization, high bandwidth linear FM radar and high resolution airborne SAR system. The system can be used as monitoring and management of earth resources such as paddy field, oil palm plantation and soil surface. First of all, the high level design will be discussed and detail design parameters are presented. It followed by radar electronics design, which outlined the detail in radar transmitter and receiver.